2023
DOI: 10.1021/acs.langmuir.3c02242
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Interacts with Cholesterol-Containing Membranes in a pH-Dependent Manner

Michael Krmic,
Escarlin Perez,
Patrick Scollan
et al.

Abstract: Aspirin has been used for broad therapeutic treatment, including secondary prevention of cardiovascular disease associated with increased cholesterol levels. Aspirin and other nonsteroidal anti-inflammatory drugs have been shown to interact with lipid membranes and change their biophysical properties. In this study, mixed lipid model bilayers made from 1-palmitoyl-2oleoyl-sn-glycero-3-phosphatidylcholine (POPC) or 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine (DOPC) comprising varying concentrations of cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…By using water as a molecular probe, the DIB offers a flexible platform to explore the influence of the lipid structure on passive permeation through bilayer aggregates. Our observations indicate that water transport across a single unsupported bilayer is highly responsive to the physical state of model membranes, revealing subtle compositional and structural effects, and selective influence of exogenous bioactive molecules. …”
mentioning
confidence: 88%
“…By using water as a molecular probe, the DIB offers a flexible platform to explore the influence of the lipid structure on passive permeation through bilayer aggregates. Our observations indicate that water transport across a single unsupported bilayer is highly responsive to the physical state of model membranes, revealing subtle compositional and structural effects, and selective influence of exogenous bioactive molecules. …”
mentioning
confidence: 88%
“…Through the use of water as a molecular probe, we illustrated that the rate at which water traverses a bilayer is highly responsive to the physical state of cell membranes. Consequently, delving into water permeability studies can significantly enrich our comprehension of the intrinsic barrier properties inherent in membrane architecture. In recent studies, we have also investigated the effects of a wide range of biologically important molecules on membrane permeability and, in turn, membrane structure. Our previous studies have shown the intriguing ability of bioactive molecules and phytochemicals to sensitively and variously respond to model membranes of diverse compositions in modulating physical properties such as transbilayer water permeability and thermodynamic, structural, and surface properties.…”
Section: Introductionmentioning
confidence: 99%
“… 43 46 In recent studies, we have also investigated the effects of a wide range of biologically important molecules on membrane permeability and, in turn, membrane structure. 47 50 Our previous studies have shown the intriguing ability of bioactive molecules and phytochemicals to sensitively and variously respond to model membranes of diverse compositions in modulating physical properties such as transbilayer water permeability and thermodynamic, structural, and surface properties.…”
Section: Introductionmentioning
confidence: 99%